2020
DOI: 10.1094/phyto-03-19-0098-le
|View full text |Cite
|
Sign up to set email alerts
|

Transfer ofXanthomonas campestrispv.arecaeandX. campestrispv.musacearumtoX. vasicola(Vauterin) asX. vasicolapv.arecaecomb. nov. andX. vasicolapv.musacearumcomb. nov. and Description ofX. vasicolapv.vasculorumpv. nov.

Abstract: We present an amended description of the bacterial species Xanthomonas vasicola to include the causative agent of banana Xanthomonas wilt, as well as strains that cause disease on Areca palm, Tripsacum grass, sugarcane, and maize. Genome-sequence data reveal that these strains all share more than 98% average nucleotide with each other and with the type strain. Our analyses and proposals should help to resolve the taxonomic confusion that surrounds some of these pathogens and help to prevent future use of inval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Another major challenge for the global production of Musaceae species is the development of cultivars resistant to biotic stressors, represented by their primary pests, the banana root borer (Cosmopolites sordidus) and the nematodes Meloidogyne spp., Pratylenchus coffeae, and Radopholus similis [13][14][15][16][17][18][19], and disease-causing pathogens, including banana bunchy top virus (BBTV) [20,21], Xanthomonas vasicola pv. musacearum causing bacterial wilt [22][23][24][25], Pseudocercospora fijiensis causing black Sigatoka [26][27][28][29], and Fusarium oxysporum f. sp. cubense (FOC) causing Fusarium wilt [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Another major challenge for the global production of Musaceae species is the development of cultivars resistant to biotic stressors, represented by their primary pests, the banana root borer (Cosmopolites sordidus) and the nematodes Meloidogyne spp., Pratylenchus coffeae, and Radopholus similis [13][14][15][16][17][18][19], and disease-causing pathogens, including banana bunchy top virus (BBTV) [20,21], Xanthomonas vasicola pv. musacearum causing bacterial wilt [22][23][24][25], Pseudocercospora fijiensis causing black Sigatoka [26][27][28][29], and Fusarium oxysporum f. sp. cubense (FOC) causing Fusarium wilt [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the species are of phytosanitary concern since they are causal agents of diseases with a global impact on seed, plant and food trade, being responsible for important economic and environmental losses [6,7]. The contours of this genus have tremendously evolved with the transfer of species into related genera (e.g., [8,9]), the description of novel species [10,11] and taxonomic rearrangements leading to synonymy of taxa [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work based primarily on DNA sequence and fatty acid data has shown that strains of Xcm have very close homology to strains of Xanthomonas vasicola and most likely belong to this species. Accordingly, the name X. vasicola has been proposed for Xcm (Aritua et al, 2008;Studholme et al, 2020), though this has not been formally approved as a new combination of names by the International Committee on Systematic Bacteriology. Therefore, the previous name Xcm is still the current official name.…”
Section: Introductionmentioning
confidence: 99%